THE ROLE OF THE TEACHER AND PARENT IN LANGUAGE DEVELOPMENT: A FOCUS ON INFANT SCHOOL - SAMKANGE, Dr. Wellington (IJRDO- Journal of Educational Research, 2016)
One of the miracles of development in education is how children learn, acquire and develop language. The school, apart from imparting knowledge and skills, has to provide for language development in learners. The paper examines the role of the teacher in language development. Different theories in development which include maturationist theory, the environmentalist theory, constructivist theory and interactionist theory are also examined. The study makes use of the mixed methodology and the case study design. The study focused on one primary school in Chegutu, Zimbabwe. The school was purposively selected. The six classes observed included two ECD classes, two grade one classes and two grade two classes. The six teachers in the selected classes automatically became respondents in the study. The study observed that while the teachers had the relevant qualifications, it was necessary for grade one and two teachers to have an understanding of ECD-A and ECD-B expectations. The study observed that teachers used a variety of approaches to promote language development in learners. The different approaches were characterised by the environmentalist theory which argues that the environment shapes learning. The study also noted that while parents played an important role in language development, the extent of their involvement in school work was influenced by their level of education and economic status. The study concluded that lack of resources, limited time, and the heterogeneous nature of languages within communities; create challenges on language development at school level. The study recommends a collective effort by schools, parents and communities for resource mobilisation and provision in order to support the teaching and learning of languages in schools.